The Development Of A Candidate Tuberclosis DNA Vaccine Expressing Mtb8.4 And Ag85B of Mycobacterium Tuberclosis [RA644.T7 M393 2007 f rb]. - Azlan, Maryam (2007)
Tuberculosis (TB) is still one of the major health problems worldwide. The only TB vaccine currently available is an attenuated strain of Mycobacterium bovis, bacille Calmette Guerin (BCG). However, the efficacy of BCG vaccine continues to be debated.